The turbulence of drug trafficking among the elite - Tondok, Santalia Banne; Pannyiwi, Rahmat; Nursinah, Andi; Kubangun, Nuraida; Zulkarnaen, Iskandar; Naim, Hardianti; Yulis, Dian Meiliani (Institute of Computer Science (IOCS), 2024)
Sidenreng Rappang Regency is the largest rice-producing area or rice barn and then this positive stigma shifted to being called a drug producer or drug barn which became one of the centers of drug trafficking in South Sulawesi Province. This research is a qualitative research that aims to find out the network pattern that allows for an increase in network cases which are the center of network operations and the mode of network operation in capturing drug abuse. The snowball sampling technique is a sampling method in which samples are obtained through a rolling and multilevel process, from one individual to another. The research location is focused on Baranti sub-district, Sidenreng Rappang district with the consideration that this area is a red zone. The results showed that there was an increase in the number of drug cases and the mode of operation of the network was highly structured and there was a positive response from the government from all components in Sidenreng Rappang.